Manajemen Laboratorium IPA di Madrasah Tsanawiyah Negeri 02 Lombok Timur - Zulkifli, Lalu; Zaki, Muhammad; Fitriani, Iwan (AS-SABIQUN, 2024)
A vital component of teaching science is laboratory administration, which is the endeavor to oversee a laboratory and learning activities. Science laboratory management is related to the managers and users of laboratory facilities and practical activities carried out in the laboratory. This study aimed to determine how planning, organizing resources and assets, implementation, supervision, and impacts arise in the management of science laboratories at MTs.N 02 East Lombok. In this study, documentation, observation, and interviews are the methods used to collect data. The results of the study are that the planning stage is quite good, the existence of short-term, medium-term, and long-term programs evidences this. Short-term programs are planned to be completed within a day, a week, or even a month. At the same time, the medium term is planned to be completed during a quarter to a semester. The Organizational Stage is the management of resources, tools, and materials available in the science laboratory. An organizational structure for managing science laboratories has been formed for the organization of resources. The Implementation Stage is the operational stage of the plan that has been scheduled. This stage is very urgent because it determines the success of achieving goals. Related to the implementation stage, the science laboratory manager at MTs. N. 02 East Lombok has done many things such as inventorying available tools and materials, making regulations, and utilization schedules that are synchronized with the madrasah program. The supervision stage functions as a controller and evaluator of the success of the implementation of laboratory management as a whole. The impacts that arise from laboratory management have been implemented well at MTs. N. 02 East Lombok.